Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1155/2012/472897
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin, a Selective Phosphodiesterase 4 Inhibitor, Effectively Suppresses Ovalbumin-Induced Airway Hyperresponsiveness without Influencing Xylazine/Ketamine-Induced Anesthesia

Abstract: Hesperetin, a selective phosphodiesterase (PDE)4 inhibitor, is present in the traditional Chinese medicine, “Chen Pi.” Therefore, we were interested in investigating its effects on ovalbumin- (OVA-) induced airway hyperresponsiveness, and clarifying its rationale for ameliorating asthma and chronic obstructive pulmonary disease (COPD). Hesperetin was revealed to have a therapeutic (PDE4H/PDE4L) ratio of >11. Hesperetin (10 ~ 30 μmol/kg, intraperitoneally (i.p.)) dose-dependently and significantly attenuated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…or 3–30 µmol/kg o.p.) reduced all types of inflammatory cells and cytokines, including IL‐5 and tumor necrosis factor‐α (TNF‐α) levels in BAL fluid of methacholine‐sensitized mice (Yang et al ., ; Shih et al ., ). Our study revealed that hesperetin–naringenin, orange, and grapefruit juices each could significantly reduce infiltration of inflammatory cells to airway and mucus plug formation.…”
Section: Discussionmentioning
confidence: 97%
“…or 3–30 µmol/kg o.p.) reduced all types of inflammatory cells and cytokines, including IL‐5 and tumor necrosis factor‐α (TNF‐α) levels in BAL fluid of methacholine‐sensitized mice (Yang et al ., ; Shih et al ., ). Our study revealed that hesperetin–naringenin, orange, and grapefruit juices each could significantly reduce infiltration of inflammatory cells to airway and mucus plug formation.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, vardenafil mimics the effect of NO by increasing GMPc levels with a subsequent reduction of histamine release and mast-cell-mediated allergic reactions [ 54 ]. Other studies reported that selective PDE4 inhibitors suppressed hematological and immunological markers of inflammation and were also effective in reducing specific airway resistance [ 55 , 56 ].…”
Section: Phosphodiesterase-5 and Inflammationmentioning
confidence: 99%
“…HSP contributes to the protective effects of orange juice to the vascular system (8,9). It was reported that HSP possesses antioxidant (10)(11)(12), hypolipidemic (13), anti-inflammatory (14), neuroprotective (15), cardioprotective (16), hypotensive (17) and anti-coagulation (18) properties, in addition to being effective in attenuating airway hypersensitivity (8,19). HSP has been demonstrated to exert vasculoprotective and anti-angiogenic effects in diabetic rats (20), in addition to inhibiting rat aortic smooth muscle cell proliferation (21).…”
Section: Introductionmentioning
confidence: 99%
“…Suggested mechanisms include the enhancement of endothelial nitric oxide production (23), suppression of reactive oxygen species production (24), inhibition of phosphodiesterases (22) and activation of tetraethylammonium-sensitive K + channels (25). Review of these studies (19,(22)(23)(24)(25) suggests that the effects mediated by HSP are likely to involve multiple targets, where each mechanism may contribute additively to the eventual vasculoprotective effect downstream. A previous study showed that HSP relaxes rat coronary arteries (RCAs) isolated from healthy rats through, at least in part, an increase of myocyte Kv channel currents (26).…”
Section: Introductionmentioning
confidence: 99%